America and guerrilla warfare - Joes, Anthony James (University Press of Kentucky, 2004)
Anthony James Joes argues that the U.S. experience in Vietnam was atypical of America's overall experience with guerrilla warfare. He examines several twentieth-century conflicts that should have better prepared the country for Vietnam: the Philippines in 1898, Nicaragua in the 1920s, Greece in the late 1940s, and the Philippines again during the Huk War of 1945-52. In a controversial interpretation, he suggests that valuable lessons were forgotten or ignored in Southeast Asia.